Self‐conscious emotions and breastfeeding support: A focused synthesis of UK qualitative research - Dawn Leeming; Joyce Marshall; Sophie Hinsliff (Wiley, 2022)
Abstract Research on women's experiences of infant feeding and related moral discourse suggests that self‐conscious emotions may be highly relevant to breastfeeding support interactions. However, the emotional impact of receiving support has not been fully explored. The aim of this review is to re‐examine qualitative UK research on receiving breastfeeding support, in order to explore the role of self‐conscious emotions and related appraisals in interactions with professional and peer supporters. From 2007 to 2020, 34 studies met criteria for inclusion. Using template analysis to identify findings relevant to self‐conscious emotions, we focused on shame, guilt, embarrassment, humiliation and pride. Because of cultural aversion to direct discussion of self‐conscious emotions, the template also identified thoughts about self‐evaluation, perceptions of judgement and sense of exposure. Self‐conscious emotions were explicitly mentioned in 25 papers, and related concerns were noted in all papers. Through thematic synthesis, three themes were identified, which suggested that (i) breastfeeding 'support' could present challenges to mothering identity and hence to emotional well‐being; (ii) many women managed interactions in order to avoid or minimise uncomfortable self‐conscious emotions; and (iii) those providing support for breastfeeding could facilitate women's emotion work by validating their mothering, or undermine this by invalidation, contributing to feelings of embarrassment, guilt or humiliation. Those supporting breastfeeding need good emotional 'antennae' if they are to ensure they also support transition to motherhood. This is the first study explicitly examining self‐conscious emotions in breastfeeding support, and further research is needed to explore the emotional nuances of women's interactions with supporters.